2001
DOI: 10.1097/00007632-200109010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Mechanism of Experimental Scoliosis in Pinealectomized Chickens

Abstract: Because there normally is evidence of lordosis in the thoracic spine of chickens, the rotational instability of the spine induced by pinealectomy may produce a scoliotic deformity as a secondary phenomenon. Pinealectomy in chickens consistently produces scoliosis with anatomic characteristics similar to those of human idiopathic scoliosis. The authors believe that disturbance of the equilibrium and the posture mechanism associated with a defect in melatonin synthesis after pinealectomy may promote the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…In animal models of idiopathic scoliosis, such as the chick experimental pinealectomy model, the development of idiopathic scoliosis-like changes has been associated with reduced levels of serum melatonin. Furthermore, administration of melatonin has been shown to prevent the development of scoliosis in both chick and rodent models [35,36]. However, in humans, studies have predominantly reported no difference in serum melatonin levels in patients with or without AIS [5,56], suggesting there would unlikely be any benefit to melatonin supplementation for patients with AIS.…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%
“…In animal models of idiopathic scoliosis, such as the chick experimental pinealectomy model, the development of idiopathic scoliosis-like changes has been associated with reduced levels of serum melatonin. Furthermore, administration of melatonin has been shown to prevent the development of scoliosis in both chick and rodent models [35,36]. However, in humans, studies have predominantly reported no difference in serum melatonin levels in patients with or without AIS [5,56], suggesting there would unlikely be any benefit to melatonin supplementation for patients with AIS.…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%
“…Those above had no radiograph or were not referred that surgical and pharmacological manipulation of laboratory animals (e.g. rabbits [69], chickens [70,71]) can produce a scoliosis similar to the human form, but what else could it resemble? A spine is either straight or it is crooked, and the variation in morphology between species is limited by the underlying structural anatomical homology.…”
Section: Aetiologymentioning
confidence: 99%
“…Pinealectomy resulted in a 100 % rate of deformity in all experiments if animals were rendered free of melatonin, the major product of the pineal gland [13,14]. Furthermore, these investigators demonstrated that development of scoliosis could be prevented by the replantation of the pineal gland in skeletal muscle or by the administration of melatonin as a replacement therapy [12], which however, could not be replicated by others [15,16]. In addition to chickens, scoliosis can be produced in pinealectomized rats and a melatonin deficient strain of mice (C57Bl6) as well, provided that they are forced to attain a bipedal posture by amputation of the forelimbs and tails [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This model was suggested by the work of Dubousset and co-workers [9] and further improved by Machida and co-workers [10][11][12]. This group of work has demonstrated that pinealectomy produced scoliosis in chickens if the surgery was performed shortly after hatching.…”
Section: Introductionmentioning
confidence: 99%